Pengembangan Bahan Ajar Mata Kuliah Gitar Tingkat Indria Secara Online di Program Studi Musik FBS UNESA - Agus Suwahyono (Universitas Negeri Surabaya, 2022)
This research was motivated by the sudden implementation of an online learning system that shocked most educators. In the future, there must be a system change policy for the implementation of online learning in every subject. The type of research used in the development of this teaching material (handout) is research and development or Research and Development (R&D). Research and information gathering initial field trials, revising test results, field trials, refinement of field test results, field implementation tests. The results of this study contained several aspects that were assessed in the form of the accuracy of the contents of the teaching materials (handouts) with the acquisition of a rating scale of 80% and 78%, the aspects of the usefulness of the teaching materials (handouts) with the acquisition of 100% and 100%, the aspects of completeness with the acquisition of a rating scale of 93% and 100%, the linguistic aspect with the acquisition of a rating scale of 80% and 73%, and the aspect of the feasibility of the content of the uku with the acquisition of a rating scale of 96%. Overall, the Indria Guitar Teaching Materials product (handout) is easy and can be defined and ready to be implemented.